A Comparative Assessment of Three Formulations of Botulinum Toxin Type A for Facial Rhytides: A Systematic Review with Meta-Analyses. Issue 4 (April 2016) - Bonaparte, James P.; Ellis, David; Quinn, Jason G.; Rabski, Jessica; Hutton, Brian
Abstract : Background: Three formulations of botulinum toxin are available for facial rhytides. It is unclear which formulation offers the greatest balance of benefits and harms. The objective of this study was to conduct a systematic review with meta-analyses to compare formulations of botulinum toxin for reduction of facial rhytides at the glabella. Methods: The authors' protocol was registered with the International Prospective Register of Systematic Reviews (CRD4201200377). A systematic literature search was performed identifying double-blind studies. The authors assessed 1-, 3-, and 4-month follow-up. The authors performed pairwise meta-analyses using random effects models to compare response rates among the three botulinum formulations and a network meta-analysis. Results: A total of 18 studies (3082 patients) were included. At 30-, 90-, and 120-day follow-up, all medications with available data showed statistically significantly increased treatment response versus placebo. Only high-dose onabotulinum toxin (compared to standard-dose onabotulinum toxin) offered additional benefit at 30 days. Exploratory analysis using network meta-analysis mostly suggested insufficient evidence of incremental benefits when comparing specific formulations. Conclusions: Evidence supporting benefits versus placebo of the different formulations was clear over time. Comparisons between active formulations were rare and typically based on single trials of small to moderate sample size. The data suggest some gains with high-dose onabotulinum toxin (relative to standard dose), whereas exploratory indirect comparisons between active formulations were largely associated with inconclusive findings. Future studies should undertake head-to-head comparisons of the different formulations and ensure longer follow-up to best inform the accumulating evidence base. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II. Abstract : Supplemental Digital Content is available in the text.